Innovation and entrepreneurship - Kennard, Mike, 1971- (London And New York: Routledge, 2021)
'The effective management of innovation and entrepreneurship is vitally important for managers, organisations and governments. This concise textbook examines strategic approaches and concepts relevant for the effective management of innovation and entrepreneurship, supported by practical insights from a variety of industry sectors. The book: Identifies the key challenges and dilemmas faced by managers and executives charged with leading, stimulating and sustaining innovation within large complex organisations; Explores the critical factors that drive entrepreneurial venture creation and growth including the search for opportunities, the management of risk and the evaluation of alternative funding sources; Considers how innovation and entrepreneurship can be facilitated through the development of technology, knowledge, intellectual property and networks Each chapter includes an essential summary of the key points, a practical example focussing on innovation and entrepreneurship in action, discussion and reflection activities, as well as further reading suggestions. Innovation and Entrepreneurship provides a practical and concise introduction for executive education students studying MSc and MBA apprenticeship programmes, as well as supplementary reading for postgraduate students studying modules on Innovation and Entrepreneurship'--
What are innovation and entrepreneurship? -- Ideas, opportunities and creativity -- New venture start-up and growth -- Developing and sustaining innovative and entrepreneurial organisations -- Knowledge management, collaboration and user-centred innovation -- Intellectual property and open innovation -- Disruptive innovation and technology management -- Strategic innovation management.
Includes bibliographical references and index.
Keywords: Technological innovations -- Management; Technological innovations -- Economic aspects; New products; Creative ability in business; Entrepreneurship